On the role of interfacial hydrogen bonds in "on-water" catalysis - Karhan, Kristof; Khaliullin, Rustam Z.; Kühne, Thomas D. (Journal of Chemical Physics, 2014)
Numerous experiments have demonstrated that many classes of organic reactions exhibit increased reaction rates when performed in heterogeneous water emulsions. Despite enormous practical importance of the observed "on-water" catalytic effect and several mechanistic studies, its microscopic origins remains unclear. In this work, the second generation Car-Parrinello molecular dynamics method is extended to self-consistent charge density-functional based tight-binding in order to study "on-water" catalysis of the Diels-Alder reaction between dimethyl azodicarboxylate and quadricyclane. We find that the stabilization of the transition state by dangling hydrogen bonds exposed at the aqueous interfaces plays a significantly smaller role in "on-water" catalysis than has been suggested previously.
CRIS-Team Scopus Importer:2023-03-20